Covid-19 Infection in Elderly with Comorbids - Yudistira, Edo; Roza Mulyana (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
The senior population has a higher risk of contracting Covid-19 and is at risk ofdeveloping more severe disease. This is due to physiological changes in old age,which causes a decrease in immune function accompanied by an increase incomorbid disorders such as diabetes, hypertension, heart disease, lung disease,and dementia. WHO reports that the mortality rate for Covid-19 patients in theelderly above 80 years in China is around 21.9%, Italy is about 89% at the ageabove 70 years, and the United States is 85% at the age of 65 years and over.Delirium syndrome often appears as the primary complaint or infrequently; itoccurs on the first day the patient is treated and shows fluctuating symptoms.Symptoms of delirium, such as disorientation, difficulty concentrating, andinattention, often occur in the elderly and are associated with a poor prognosis.Management of geriatric patients with covid 19 must be carried out thoroughlyand completely, especially in geriatric patients with comorbidities. Managementincludes primary diseases, namely Covid-19 infection, delirium, nutritionaltherapy, blood sugar, family education for patient assistance, maintaining thepatient's body and environment cleanliness, oral hygiene, and, last but not least,moral support from the family for the patient. With complete management, elderlypatients with various comorbid can survive the Covid-19 infection.